OBSERVING THE PATTERNS OF CAREER DEVELOPMENT POST OCCUPATIONAL TRANSFORMATION - I Nyoman Try Artha Windayana; Anak Agung Gede Putra Pemayun (LPSDI Bina Patria, 2023)
The early period of President Joko Widodo's leadership and Vice President KH. Maaruf Amin in 2019 included Simplification of Positions in the government bureaucracy as one of the priority work programs. The bureaucratic simplification policy is in the form of simplifying positions to only two levels. ASNs holding positions below the 2 (two) levels will be transformed into certain functional positions. This very big change will certainly have a big influence on ASN's future career development. In order to find out how Career Development is implemented, this study uses the theory of Career Development according to Hasto Nur Joko Utomo and Meilan Sugiarto which provides indicators of Career Development namely (1) Employee and Organizational Relations; (2) Employee Personnel; (3) External Factors; (4) Politics in Organizations; (5) Award System; (6) Number of Employees; (7) Organization Size. So that the aims of this study are (1) to know and describe the Implementation of Position Transformation in the Provincial Government of Bali; (2) Analyze and Describe ASN Career Development Patterns; (3) Knowing and Analyzing Obstacles in ASN Career Development. In this study using a qualitative descriptive approach using observation data collection techniques, interviews and documentation. The results of the study show that the Provincial Government of Bali has carried out job transformations of 529 Administrative Officers. Then, all the career development indicators used will determine career development for ASN. The principle of career development in the Minister of Administrative and Bureaucratic Reform Regulation on Civil Servant Career Patterns has also been fulfilled. However, there are several obstacles that can hinder career development including (1) Mindser ASN; (2) Assessment of Credit Scores; (3) Regulations; (4) Minimal Socialization. The conclusion in this study is that the Provincial Government of Bali has implemented a policy of Simplifying Bureaucracy and Pruning Organizational Structures through Position Transformation into Functional Positions, even though all career development indicators and principles have been implemented but there are still obstacles in their application in the implementations.